Production of Pentaerythritol Monoricinoleate (PEMR) by immobilized Candida antarctica lipase B - Manish G. Yadav; Rajeshkumar N. Vadgama; Monali R. Kavadia; Annamma Anil Odaneth; Arvind M. Lali (Biotechnology Reports, 2019)
In the present study, green synthesis of pentaerythritol monoricinoleate (PEMR) was carried out using Candida antarctica lipase B immobilized on hydrophobic adsorbent via interfacial activation. Various reaction parameters such as reaction time, organic solvent, molar ratio, the enzyme load, and presence of molecular sieves on pentaerythritol (PE) ester synthesis were systematically studied to yield selective monoester of PE. The strategies (smart use of substrate molar ratio and polar organic solvent) were employed to suppress dimerization of ricinoleic acid (RA) to avoid by-product formation and hence to obtain superior mono-ester yield. Under optimized conditions viz. substrate molar ratio of 4 (PE):1 (RA) with 2% enzyme load and 200 g/L molecular sieves in the presence of tert-butanol, 93% substrate molar conversion in 24 h reaction time was obtained. The synthesized PEMR was also characterized using FT-IR and Mass spectroscopy. To the best of our knowledge, this is the first report describing the enzymatic synthesis of PEMR. Keywords: Pentaerythritol, Ricinoleic acid, Pentaerythritol monoricinoleate, Lipase, Green synthesis